2006
DOI: 10.1373/clinchem.2006.068783
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Risk Figures in 2nd-Trimester Maternal Serum Screening for Down Syndrome: Comparison of 2 Laboratories

Abstract: Background: Analytical error affects 2nd-trimester maternal serum screening for Down syndrome risk estimation. We analyzed the between-laboratory reproducibility of risk estimates from 2 laboratories. Methods: Laboratory 1 used Bayer ACS180 immunoassays for ␣-fetoprotein (AFP) and human chorionic gonadotropin (hCG), Diagnostic Systems Laboratories (DSL) RIA for unconjugated estriol (uE3), and DSL enzyme immunoassay for inhibin-A (INH-A). Laboratory 2 used Beckman immunoassays for AFP, hCG, and uE3, and DSL enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Serum screening has shown to be cost-effective for detecting Down syndrome (23 ) and can reduce the need for invasive amniocentesis (24,25 ). However, recent studies revealed poor accuracy and imprecision of RIA in measuring uE 3 compared with results obtained from liquid chromatographytandem mass spectrometry (LC-MS/MS) analyses, and poor agreement of uE 3 concentrations was observed between RIA and chemiluminescent immunoassay methods (26,27 ). More importantly, discrepancies in assay performance of various kits that cannot be normalized by applying multiples of the median (MoMs) could impact the accuracy of the risk estimation for Down syndrome (27)(28)(29)(30).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Serum screening has shown to be cost-effective for detecting Down syndrome (23 ) and can reduce the need for invasive amniocentesis (24,25 ). However, recent studies revealed poor accuracy and imprecision of RIA in measuring uE 3 compared with results obtained from liquid chromatographytandem mass spectrometry (LC-MS/MS) analyses, and poor agreement of uE 3 concentrations was observed between RIA and chemiluminescent immunoassay methods (26,27 ). More importantly, discrepancies in assay performance of various kits that cannot be normalized by applying multiples of the median (MoMs) could impact the accuracy of the risk estimation for Down syndrome (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…However, recent studies revealed poor accuracy and imprecision of RIA in measuring uE 3 compared with results obtained from liquid chromatographytandem mass spectrometry (LC-MS/MS) analyses, and poor agreement of uE 3 concentrations was observed between RIA and chemiluminescent immunoassay methods (26,27 ). More importantly, discrepancies in assay performance of various kits that cannot be normalized by applying multiples of the median (MoMs) could impact the accuracy of the risk estimation for Down syndrome (27)(28)(29)(30). Concerns regarding poor accuracy of RIA, EIA, or ELISA methods in uE 3 testing have also been raised in the fields of epidemiology and breast cancer risk assessment (17,31 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan bir çalışmada farklı iki laboratuvar da aynı serum çalışılmış fakat sonuçlar istatistiksel olarak ileri düzey-de anlamlı bulunmuştur. Aradaki farkın laboratuvarlarda kullanılan yöntem farklılığından kaynaklandığı ifade edilmiştir [20].…”
Section: Discussionunclassified
“…3,4,14 This study both assessed stabilization of samples and evaluated variations due to using different Instruments.…”
Section: Figurementioning
confidence: 99%